2003
DOI: 10.1074/jbc.m309467200
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biophysical Characterization of a Multidomain Peptide from a Saccharomyces cerevisiae G Protein-coupled Receptor

Abstract: We attached peptides corresponding to the seventh transmembrane domain (TMD7) of the ␣-mating factor receptor (Ste2p) of Saccharomyces cerevisiae to a hydrophilic, 40-residue fragment of the carboxyl terminus of this G protein-coupled receptor. Peptides corresponding to (a) the 40-residue portion of the carboxyl tail (T-40), (b) the tail plus a part of TMD7 (M7-12-T40), and (c) to the tail plus the full TMD7 (M7-24-T40) were chemically synthesized and purified. The molecular mass and primary sequence of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 31 publications
1
22
1
Order By: Relevance
“…They allow for structure elucidation of hydrophobic TM sequences in the absence of hydrophilic flanks (Tomich et al, 1998;Naider et al, 2003). In at least one case , helix formation by an isolated TM segment could hence be shown to be independent of flanking hydrophilic residues (however, see Sections 3.2 and 5.2 for examples where this is not the case).…”
Section: Structure and Oligomerization Of Tm Peptides In Organic Solvmentioning
confidence: 98%
“…They allow for structure elucidation of hydrophobic TM sequences in the absence of hydrophilic flanks (Tomich et al, 1998;Naider et al, 2003). In at least one case , helix formation by an isolated TM segment could hence be shown to be independent of flanking hydrophilic residues (however, see Sections 3.2 and 5.2 for examples where this is not the case).…”
Section: Structure and Oligomerization Of Tm Peptides In Organic Solvmentioning
confidence: 98%
“…As with early studies on oligoalanines,16, 18 polyethylene glycol has also been used to solubilize a transmembrane peptide 74. Recently we have explored the use of the extracellular and cytosolic termini of GPCRs, which naturally exist in the aqueous milieu outside the membrane core, as solubilizing templates 24, 75. The goal of this approach is to use natural elements of the receptor to improve the solubility of the transmembrane domains.…”
Section: Part Iii: Solubilizing Regions Of Membrane Proteinsmentioning
confidence: 99%
“…Recently, we chemically synthesized a 64-residue multidomain peptide containing the seventh transmembrane domain and 40 residues of the cytosolic terminus of Ste2p and showed that this peptide retained distinct structural characteristics for each of these domains in organic-aqueous medium and various detergents using circular dichroism analyses. Moreover, CD patterns in detergents were nearly identical at peptide concentrations from 50 to 500 µM indicating that NMR analyses were feasible (40).…”
mentioning
confidence: 98%